2016
DOI: 10.1002/adsc.201600297
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)‐ or Rhodium(III)‐Catalyzed Grignard‐Type Addition of Indolines and Indoles to Activated Carbonyl Compounds

Abstract: The ruthenium(II)‐ or rhodium(III)‐catalyzed pyrimidinyl‐directed Grignard‐type C−H additions of N‐heterocycles with activated aldehydes and ketones are described. A cationic ruthenium catalyst and sodium acetate additive in dichloroethane as solvent were found to be optimal catalytic system for the construction of C‐7 alkylated indolines. In sharp contrast, a cationic rhodium complex allows the generation of C‐2 alkylated indoles and pyrroles as well as C‐1 alkylated carbazoles. The site‐selective C−H functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…13 The alcohol products were obtained in good yield when electron-rich groups or halogen substituents were placed around the aromatic portion of the indoline ring. The reaction also tolerated alkyl and aryl functionality at the C2 and C3 positions.…”
Section: Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The alcohol products were obtained in good yield when electron-rich groups or halogen substituents were placed around the aromatic portion of the indoline ring. The reaction also tolerated alkyl and aryl functionality at the C2 and C3 positions.…”
Section: Aldehydesmentioning
confidence: 99%
“…13 The indole heterocycle class was the most extensively evaluated, and functionalization selectively occurred at the C2 position. A range of electron-rich and electron-poor functionality was compatible at the C3–C7 positions, and the alcohol products were obtained in high yield.…”
Section: Aldehydesmentioning
confidence: 99%
“…By using a pyrimidine as an directing group, the Kim laboratory has recently demonstrated that heterocycles of indolines, indoles, pyrroles, and carbazoles underwent site‐selective C−H bond addition to trifluoropyruvates under rhodium catalysis to provide the corresponding tertiary alcohols 177 in good yields (Scheme ). It is noteworthy that indolines favor the C−H functionalization at C7 position, while indoles are selectively functionalized at C2 position.…”
Section: O‐substituted Quaternary Centersmentioning
confidence: 99%
“…Meanwhile, the groups of Bach, [5a,c,e] Ackermann, [5b,d,f] Punji [5g,i,j] and Shi [5h] have independently developed C2−H alkylation of indoles with alkyl halides using Pd, Ni, Co and Mn catalysts. Such a transformation has also been successfully implemented by using 2‐vinyloxiranes, [6a] alkyltrifluoroborates, [6b,h,i] diazo compounds, [6c,g] alkylarenes, [6d,j] cyclopropanols, [6e] carbonyl compounds, [6f] imines [6k] and acetonitrile derivatives [6l] . Despite the impressive progress made so far, the development of new and efficient strategies to access C2‐alkylated indoles with readily available alkylation reagents is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%